EFFECTIVENESS OF ELEMENTS PERIODIC TABLE INTERACTIVE MULTIMEDIA IN NGUYEN TAT THANH HIGH SCHOOL - Astuti, Fiki Kusuma; Cahyono, Edy; Supartono, Supartono; Van, Ngoc Chau; Duong, Nguyen Thuy (Sanata Dharma University Yogyakarta, 2018)
The result of observation and interview shows that the learning process in Nguyen Tat Thanh High School was going fun and everyday teacher used different method of learning, sometimes teacher also made a worksheet for students, but the power point presentation media that teacher used did not show the interaction between media, teacher and students. Also there were unnecessary pictures on the power point that could distract students focus and the colour combination was not suitable. This research aimed to develop an interactive multimedia and know its feasibility and effectiveness. This study had significance to develop an alternative instructional multimedia in an education game way so could increase students’ motivation and learning outcome. The design of this research was Research and Development with ADDIE model. The data of this research were obtained from validation result from media expert and instructional expert, students’ response at small scale test, post test result and students’ response at large scale test. The score of validation result for the media expert was 96 categorized as very feasible and for the instructional expert was 62 categorized as feasible. Small scale test result showed that students gave very good response with 69.97 score. Students’ post test gave effective result with classical completeness 61.76% and very good response with 68.5 score. It can be concluded that the elements periodic table interactive multimedia was feasible and effective to be used in learning process, and have very good response from the students as users. DOI: https://doi.org/10.24071/ijiet.2018.020101